A Comparison of Dielectric Properties of Palm Oil with Mineral and Synthetic Types Insulating Liquid under Temperature Variation - Rajab, Abdul; Sulaeman, Aminuddin; Sudirham, Sudaryatno; Suwarno, Suwarno (ITB Journal Publisher, LPPM ITB, 2011)
Mineral oil is known to have a low biodegradability level and high susceptibility to the fire. These conditions motivate many researchers to look for alternative sources for insulating oil. One of the alternative liquid is palm oil. To verify the suitability of using palm oil as an insulating liquid, it is important to make dielectric properties comparison with the commonly used insulating liquid. This paper presents comparison of temperature effect on dielectric properties of palm oil with mineral type insulating liquid and silicone oil. The measured parameters were breakdown voltage, dissipation factor (tan δ), and dielectric constant. Breakdown voltage measurement was performed in accordance with IEC 156 standard, whereas, the dissipation factor and dielectric constant measurement were conducted based on IEC 60247 standard test methods. The results showed that variations of dielectric properties of palm oil to the temperature change, in general, have the same tendency with those of commonly used insulating liquids i.e. mineral oil and silicone oil. Breakdown voltages and dissipation factors of all tested oils were increased, while their dielectric constants were slightly decreased with the increase of temperature.